2011
DOI: 10.1124/mol.110.069542
|View full text |Cite
|
Sign up to set email alerts
|

Different Residues in the GABAAReceptor Benzodiazepine Binding Pocket Mediate Benzodiazepine Efficacy and Binding

Abstract: Benzodiazepines (BZDs) exert their therapeutic actions by binding to the GABA A receptor (GABA A R) and allosterically modulating GABA-induced chloride currents (I GABA ). A variety of ligands with divergent structures bind to the BZD site, and the structural mechanisms that couple their binding to potentiation of I GABA are not well understood. In this study, we measured the effects of individually mutating 22 residues throughout the BZD binding pocket on the abilities of eszopiclone, zolpidem, and flurazepam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 42 publications
2
46
0
6
Order By: Relevance
“…Previous mutations, specifically a1(S205) and a1(S206) [equivalent to nAChR b2(D217) and b2(D218)], g2(Y72), g2(D75), and g2(F78) [equivalent to nAChR a4(M83), a4(N860), and a4(V89)] located in the GABA A R BZD-binding site have been shown to increase or decrease GABA potency (Teissere and Czajkowski, 2001;Morlock and Czajkowski, 2011). Similarly, several recent studies have shown that mutation of residues a3(E173), a3(L158), a3(A179), a3(K183), b2(R46), and b2(A127) located in nonorthosteric interfaces of the rat a3-and b2-nAChR subunits also increase or decrease ACh potency from 2-to 60-fold compared with wild-type a3b2-nAChR (Chrisman et al, 2014;Short et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Previous mutations, specifically a1(S205) and a1(S206) [equivalent to nAChR b2(D217) and b2(D218)], g2(Y72), g2(D75), and g2(F78) [equivalent to nAChR a4(M83), a4(N860), and a4(V89)] located in the GABA A R BZD-binding site have been shown to increase or decrease GABA potency (Teissere and Czajkowski, 2001;Morlock and Czajkowski, 2011). Similarly, several recent studies have shown that mutation of residues a3(E173), a3(L158), a3(A179), a3(K183), b2(R46), and b2(A127) located in nonorthosteric interfaces of the rat a3-and b2-nAChR subunits also increase or decrease ACh potency from 2-to 60-fold compared with wild-type a3b2-nAChR (Chrisman et al, 2014;Short et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the predominant heteromeric receptors where the binding interfaces will differ, such ligands may possibly serve as positive or negative allosteric modulators at sites distinct from those occupied by agonist and competitive antagonist (36). Such appears to be the case for the benzodiazepines (36,37) and other sedative agents (38) that act in this manner with the GABA receptor (39,40). Accordingly, new dimensions for achieving pharmacologic selectivity for particular nAChR subtypes may result with the cooperative nAChR ligands possessing electron-rich substituted 2-aminopyrimidines.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations to this interface can have large effects on binding affinity and/or efficacy of benzodiazepine ligands Padgett and Lummis, 2008;Morlock and Czajkowski, 2011). In particular, residues of loop F of the ␥2 subunit appear to play an important role in defining the efficacy of benzodiazepine ligands Padgett and Lummis, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Benzodiazepines potentiate the GABA A receptor through interactions with the ␣-␥ subunit interface at which several loop F residues have been shown to affect the efficacy of several benzodiazepine ligands (Padgett and Lummis, 2008;Morlock and Czajkowski, 2011). We tested the possibility that the MTSES molecule occupies the benzodiazepine binding cavity, thereby imitating the effect of a bound benzodiazepine and underlying the enhanced current response after exposure to MTSES.…”
Section: Mtses Modification After Occupation Of Allosteric Binding Simentioning
confidence: 99%